A Rare Case of Extra-abdominal Desmoid Fibromatosis of the Mandible in a 9-Year-Old Child - Madi, Medhini; Bhat, Supriya; Madiyal, Ananya; Babu, Subhas G. (Journal of Health and Allied Sciences NU, 2021)
Desmoid tumors are tumors of the fibrous tissue that are benign, which most commonly occur in the abdominal walls of females who are of childbearing age. The most common location for extra-abdominal desmoid tumors is the shoulder and the upper limb. They show no tendency for metastasis but are locally very aggressive. Here we report a rare case of extra-abdominal desmoid fibromatosis in the mandible of a child.
Keywords: desmoid fibromatosis; extra-abdominal; benign tumor